2018
DOI: 10.1097/jtn.0000000000000395
|View full text |Cite
|
Sign up to set email alerts
|

A Diaphragmatic Hernia and Pericardial Rupture Caused by Blunt Injury of the Chest: A Case Review

Abstract: Blunt traumatic diaphragmatic hernias are most commonly seen in combination with other injuries. Right diaphragmatic ruptures with serious pericardium ruptures are relatively rare. The diagnosis of diaphragmatic hernias is not difficult; however, prior to surgery, it is difficult to judge whether pericardium damage has occurred, particularly on the right side. This injury may occur in a critical pathological state in which cardiac tissue is outside the pericardium due to the pericardial defect. Severe hemodyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The rupture of the pericardium in blunt chest trauma is also very rare [ 13 ]. Deceleration forces are usually responsible for the occurrence of pericardial defect, since the base of the heart is more fixed to the pulmonary vasculature and aorta, while the apex is more mobile, causing the rupture mostly on the lateral side of pericardium [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rupture of the pericardium in blunt chest trauma is also very rare [ 13 ]. Deceleration forces are usually responsible for the occurrence of pericardial defect, since the base of the heart is more fixed to the pulmonary vasculature and aorta, while the apex is more mobile, causing the rupture mostly on the lateral side of pericardium [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rupture of the pericardium in blunt chest trauma is also very rare [ 13 ]. Deceleration forces are usually responsible for the occurrence of pericardial defect, since the base of the heart is more fixed to the pulmonary vasculature and aorta, while the apex is more mobile, causing the rupture mostly on the lateral side of pericardium [ 13 ]. Pericardial rupture is seen in less than 0.5% of patients presenting after blunt trauma, and cardiac herniation through a pericardial defect is a potential complication of this injury [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rupture of the pericardium in blunt chest trauma is also very rare [14]. It almost always leads to some degree of cardiac herniation through pericardial defect.…”
Section: Discussionmentioning
confidence: 99%
“…It almost always leads to some degree of cardiac herniation through pericardial defect. Deceleration forces are usually responsible for occurrence of pericardial defect, due to reason that base of the heart is more xed to the pulmonary vasculature and aorta, while apex of the heart is more mobile, causing the rupture mostly on the lateral site of pericardium during trauma [14]. The clinical ndings could vary from mild symptoms to the very severe, especially if the rupture causes the obstruction of huge blood vessels (pulmonary or coronary artery) [15].…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that 40%, 25%, and 5% of patients had blunt diaphragmatic injuries with pelvic fracture, spleen and liver injuries, and thoracic aortic injuries, respectively [ 5 ]. Only a few cases of isolated rupture of the pericardium or combined diaphragmatic and pericardial ruptures have been reported [ 6 ]. Also, few cases of pericardial tear with intra-pericardial diaphragmatic hernia have been reported [ 7 ].…”
Section: Discussionmentioning
confidence: 99%